CONSTRUCTING WORK ETHICS AND GENERAL HUMAN ETHICS PARADIGM IN INDONESIA - Muhammad Gunawan Wibisono; Sundjoto; Sri Rahayu; Muhammad Andri Radiany; Purwanto; Anita Kartika Sari; Rika Yuliastanti (Politeknik Ubaya, 2024)
This research explores the significance of work ethics and general human ethics in the context of employee development within the corporate industry. Through an extensive review of literature encompassing 140 research findings, the study emphasizes the crucial role of employee development in enhancing human resource quality and company productivity. The research identifies key factors contributing to effective employee development, including the identification of employee needs and potentials, provision of training and coaching, utilization of technology, provision of constructive feedback, and regular evaluations. Furthermore, the research underscores the importance of adapting development programs to meet the specific needs of employees and their work environments. It highlights the pivotal role of managers and supervisors in providing support and guidance to employees throughout the development process. Additionally, the research emphasizes the significance of evaluating the effectiveness of employee development programs to ensure continual improvement and success. By integrating these findings into corporate practices, companies can design and implement more effective employee development initiatives tailored to their workforce. This, in turn, will lead to improved employee performance, strengthened competencies, and ultimately, enhanced company growth and sustainability. Copyright © 2024 by Authors, Published by Jurnal Bisnis Terapan. This work is licensed under a Creative Commons. Attribution-ShareAlike 4.0 International License.